Intensity of statin therapy after ischaemic stroke and long-term outcomes : a nationwide cohort study - Kytö, Ville; Åivo, Julia; Ruuskanen, Jori O (BMJ on behalf of the Chinese Stroke Association, 2025)
Background Statins are essential for secondary prevention after ischaemic stroke (IS). However, statin intensity recommendations differ, and there is a concern about intracerebral haemorrhage (ICH). We studied the long-term impacts of initial statin intensity following IS.
Methods Consecutive patients using high-intensity, moderate-intensity or low-intensity statin early after IS (n=45 512) were retrospectively studied using national registries in Finland. Differences were adjusted using multivariable regression. The primary outcome was all-cause death within 12-year follow-up (median 5.9 years). Secondary outcomes were recurrent IS, cardiovascular death and ICH studied using competing risk analyses.
Results High-intensity therapy was initially used by 16.0%, moderate-intensity by 73.8% and low-intensity by 10.2%. Risk of death was lower with high-intensity versus moderate-intensity (adjusted HR (adj.HR) 0.92; 95% CI 0.87 to 0.97; number needed to treat (NNT) 32.0), with moderate-intensity versus low-intensity (adj.HR 0.91; 95% CI 0.87 to 0.95; NNT 27.5) and with high-intensity versus low-intensity (adj.HR 0.83; 95% CI 0.78 to 0.89; NNT 14.6) statin. There was a dose-dependent association of initial statin intensity with a lower probability of recurrent IS (p<0.0001) and cardiovascular death (p<0.0001). The occurrence of ICH was not associated with initial statin intensity (p=0.646).
Conclusions Following IS, more intense initial statin treatment is associated with improved long-term outcomes but not with the risk of ICH. These findings emphasise the importance of high statin intensity shortly after IS.